Is zero rating the end of net neutrality and the open internet? An analysis of business practices and policy approaches. (1st September 2021) - Aerssens, Janneke; Donders, Karen; Trappel, Josef
The open internet and net neutrality are intertwined. People debate whether net neutrality safeguards part of the open internet or not. The commercial aspect is paramount. Zero rating is one of these practices that is often discussed, especially in relation to developing countries. The open internet regulation addresses commercial practices. It is, however, vague and can be interpreted in multiple ways. To answer the question if zero rating is going against net neutrality or if it enables net neutrality, five case studies were analysed and 18 experts interviewed. To support the case studies, documents were analysed. In certain circumstances, it is useful to zero rate information. Zero rating mostly violates net neutrality and the open internet, because of its imbedded discrimination. Some zero rating offers are beneficial and do not harm competition. This mostly concerns offers evolving around e-learning, health and government information.